Déchiffrages. Quelques réflexions sur l’écriture libyco-berbère - Dominique Casajus (Afriques)
The Tuareg use alphabets with characters called tafineq (plural: tifinagh). Some writers have, rightly or wrongly, related this word’s root (FNQ) to the word used by the Greeks to refer to the Phoenicians. These alphabets derived from much older ones, which are usually said to be “Libyan” or “Libyco-Berber”. Libyco-Berber inscriptions are found throughout a region stretching from Libya to Morocco and even the Canary Islands — sometimes along with Punic or Latin engravings. Owing to the discovery in Dougga (Tunisia) of two bilingual Libyco-Punic inscriptions dating from the 2nd century BC, one of the variants of the Libyco-Berber alphabet has been partly deciphered. Moroccan inscriptions are probably older, but the dates proposed for them are to be used with caution. Two recent studies, the one devoted to contemporary rock inscriptions and the other to the evolution of Libyco-Berber scripts from Ancient Times up till the present, are reviewed; and a few hypotheses related to the dating of engravings are discussed as well as the circumstances of the initial discovery made in Dougga.